ПЕДАГОГИКА ОЛИЙ ТАЪЛИМ МУАССАСАЛАРИ ТАЛАБАЛАРИНИНГ АХБОРОТ КОМПЕТЕНТЛИГИНИ РИВОЖЛАНТИРИШНИНГ БАЪЗИ БИР УСУЛЛАРИ - Қыдырниязов, А. (SCIENCE and SOCIETY, 2019)
The article deals with the issues of students’ information competence. One of the directions of informatization of education is informing students about information competence. Despite the research, the practice shows that the problem of students’ information competence remains unsolved. According to the author, the ability of students to learn can have a solid foundation, and the ability to use this knowledge can be used wisely.